PENGARUH SERVANT LEADERSHIP, DISIPLIN KERJA DAN KEPUASAN KERJA TERHADAP KINERJA KARYAWAN PADA PT BFI FINANCE CABANG DENPASAR - I Made Adi Diantara; I Wayan Sujana; Ni Nyoman Ari Novarini (Program Studi Manajemen Fakultas Ekonomi dan Bisnis UNMAS, 2024)
This research evaluates the influence of servant leadership, work discipline, and job satisfaction on employeeperformance at PT BFI Finance Denpasar Branch. The research used a total sampling technique, involving 36 respondents. Data analysis using multiple linear regression produced findings that servant leadership, work discipline, and job satisfaction positively and significantly influence employee performance. The application of good servant leadership contributes to increased performance, as does a high level of work discipline. Job satisfaction has also been proven to have apositive impact on employee performance, showing that satisfied employees tend to provide better performance. Research limitations focus on specific variables, and suggestions for improvement include leadership style, work discipline, andpromotion policies. Thus, corrective actions are expected to significantly improve employee performance at PT BFI FinanceDenpasar Branch.